2002
DOI: 10.1038/sj.ejcn.1601292
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of habitual energy and macronutrient intake in adults: comparison of a seven day food record with a dietary history interview

Abstract: Objective: To examine the quantitative agreement between a 7 day food record and a diet history interview when these are conducted under the same conditions and to evaluate whether the two methods assess habitual diet intake differently among subgroups of age and body mass index (BMI). Design: Cross-sectional study. Setting: Population study, Denmark. Subjects: A total of 175 men and 173 women aged 30 -60 y, selected randomly from a larger population sample of Danish adults. Interventions: All subjects had hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 24 publications
(25 reference statements)
2
41
0
1
Order By: Relevance
“…Although it has been recommended to use 7-days' food records as the 'gold standard' when investigating the relative validity of a FFQ (Willett, 1998), the diet history and 7-days' food record have interchangeably served as 'gold standards' in practice (Willett et al, 1985;Block et al, 1990;Jain et al, 1996;Hoidrup et al, 2002) and both Black et al (2000) and Hoidrup et al (2002) have illustrated a close quantitative agreement between the two methods, and the difference between the methods in assessing energy and macronutrient intake seems to be negligible. Because of logistic problems associated with the diet record methods the diet history was chosen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been recommended to use 7-days' food records as the 'gold standard' when investigating the relative validity of a FFQ (Willett, 1998), the diet history and 7-days' food record have interchangeably served as 'gold standards' in practice (Willett et al, 1985;Block et al, 1990;Jain et al, 1996;Hoidrup et al, 2002) and both Black et al (2000) and Hoidrup et al (2002) have illustrated a close quantitative agreement between the two methods, and the difference between the methods in assessing energy and macronutrient intake seems to be negligible. Because of logistic problems associated with the diet record methods the diet history was chosen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a previous study, reproducibility of the 7-day food record for dietary habits regarding macronutrients was evaluated and found to be high (19). On the other hand, under-reporting of dietary energy intake was also found to be related to the degree of obesity (20,21). However, if, in fact, the obese under-reported total energy intake more so than the lean and overweight participants in the present study, and if under-reporting is related to their BW, the observed associations found among the obese would be conservative, rather than overestimated, suggesting that our results among the obese men and women are, at best, conservative.…”
Section: Discussionmentioning
confidence: 99%
“…Validation studies including DLW measurements during the last decade have demonstrated that dietary methods are often biased towards underestimation of intake in adolescents (Livingstone & Robson, 2000) as well as adults (Livingstone & Black, 2003). Several studies have shown that the recording method was biased towards under-reporting of intake (Livingstone et al, 1992;Bratteby et al, 1998), especially in subjects with high BMI (Bandini et al, 1990;Price et al, 1997;Høidrup et al, 2002). Lower EI/BMR have been shown for registration methods than for DH in studies on children and adolescents (Livingstone & Robson, 2000).…”
Section: Discussionmentioning
confidence: 99%